The attractiveness of Bukit Nanas recreational forest as an ecotourism destination as perceived by foreign visitors - Aziz, Azlizam; Idris, Nur Hafizah; Jamaludin, Mazlina; Mariapan, Manohar; Samdin, Zaiton (Asian Economic and Social Society, 2017)
Ecotourism has been identified by the Malaysian government in its newly introduced National Key Economic Area as an important niche area, in which ecotourism would be used to differentiate Malaysia from other competing destinations in the region. Conventionally, ecotourism products are developed based on the existing cultural and natural attractions. In Malaysia, recreational forest have the potential to be developed and marketed as ecotourism destinations since these forests are endowed with many attributes of tourism attractions, including beautiful scenery, fresh-flowing rivers, waterfalls as well as diverse flora and fauna. There are currently a total of 124 recreational forests in Peninsular Malaysia which has received visitations by mostly local visitors and only a handful of foreigners. Thus, the principal purpose of this paper is to evaluate the relative importance of existing attributes in attracting foreign tourist to visit recreational forests. Several factors are noted as having the potential to influence future visits to the recreational forest. These factors include the vast diversity of natural resources, proximity to major cities where captured tourism markets are situated and the availability of facilities.